Adaptation of lodgepole pine and interior spruce to climate: implications for reforestation in a warming world. (19th January 2016) - Liepe, Katharina J.; Hamann, Andreas; Smets, Pia; Fitzpatrick, Connor R.; Aitken, Sally N.
Abstract: We investigated adaptation to climate in populations of two widespread tree species across a range of contrasting environments in western Canada. In a series of common garden experiments, bud phenology, cold hardiness, and seedling growth traits were assessed for 254 populations in the interior spruce complex ( Picea glauca, P. engelmannii, and their hybrids) and for 281 populations of lodgepole pine ( Pinus contorta ). Complex multitrait adaptations to different ecological regions such as boreal, montane, coastal, and arid environments accounted for 15–20% of the total variance. This population differentiation could be directly linked to climate variables through multivariate regression tree analysis. Our results suggest that adaptation to climate does not always correspond linearly to temperature gradients. For example, opposite trait values (e.g., early versus late budbreak) may be found in response to apparently similar cold environments (e.g., boreal and montane). Climate change adaptation strategies may therefore not always be possible through a simple shift of seed sources along environmental gradients. For the two species in this study, we identified a relatively small number of uniquely adapted populations (11 for interior spruce and nine for lodgepole pine) that may be used to manage adaptive variation under current and expected future climates.